Phenylacetic acids were detected in the plasma and urine of rats administered with low-dose mulberry leaf extract - Lee, C.Y.; Sim, S.M.; Cheng, H.M. (2008)
The use of a high quercetin dose to demonstrate its absorption and bioavailability does not reflect the real dietary situation because quercetin glycosides are usually present in small amounts in the human diet. This study aimed to demonstrate the absorption and bioavailability of quercetin in mulberry leaves that represents a more physiologic dietary situation. Mulberry leaf ethanol extract was prepared similar to tea inftision, which is the way the tea leaves are generally prepared for consumption. Accordingly, rats were fed by oral intubation the mulberry leaf ethanol extract (15 g / rat per day) or pure rutin (135 mu g/rat per day) for 2 weeks. The control group received a similar volume of the vehicle, 10 ethanol. There was a significant increase in total antioxidant activity (TAA) in the urine and feces of the antioxidants-fed rats. Phenylacetic acid, a microbial metabolite of quercetin, was detected in the urine of the test animals, and quercetin was present in the fecal samples. By using an in situ intestinal preparation, 3-hydroxyphenylacetic acid, another microbial metabolite of quercetin, was detected in the plasma when the duodenal segment was instilled with 2 mg of rutin. This microbial metabolite retained 50 of the TAA of quercetin. The results of this study indicate that in a more realistic dietary situation, an increase in TAA in the body after consumption of quercetin-containing foods is contributed mainly by the microbial metabolites. (C) 2008 Elsevier Inc. All rights reserved.